THE INFULENCE OF FINANCIAL CONDITIONS AND SHARIA SUPERVISORY BOARD TOWARD CORPORATE TAXPAYER COMPLIANCE - Hevi Oktiawati (University of Sang Bumi Ruwa Jurai, 2020)
The purpose of this research is to determine whether the financial condition and sharia supervisory board have a significant influence on the compliance of corporate taxpayers either partially or simultaneously. The samples are selected by purposive sampling method so that 9 sharia commercial bank samples are obtained. The unit of analysis in the study amounted to 45 annual reports of Islamic banks. The type of quantitative data is in the form of financial reports (annual reports) of each bank from 2014- 2018. The results of this study find that financial conditions affect the compliance of corporate taxpayers, indicated the better financial condition, the greater the profits obtained, the better the compliance of corporate taxpayers. Sharia Supervisory Board affects the compliance of corporate taxpayers, it is indicated that the better the one in supervising a bank, the better and obedient the company is in compliance with corporate taxpayers.